The Breath Sport Training for Health - M.C. Tri Atmodjo (Bandar Lampung University (UBL), 2014)
Since 1993 I have been training of breath sport. Along this time good health always with me as well.Sometime the result of this training also able to help my family (my children mainly) to solve his/her illness. This training held 3 times a week with 2 hours respectinely. The Faculty of Medicine in University of Airlangga in Surabaya East Java has the laboratory which able to prove the influence of breath training to our health. This laboratory able to show us that before training and after training of breath sport showed significant different which better health to someone after training with exelence regulation.